Securities in Peruvian jurisprudence - Távara Córdova, Francisco (2024)
In this article, I present certain comments regarding some executive orders issued, mainly, by the Permanent Civil Chamber of our Supreme Court of Justice of the Republic, the highest jurisdictional body that I had the honor of integrating and presiding over for several years; Likewise, I also pay attention to sentences debated by the Constitutional Court. It is worth mentioning that my modest contribution is intended to ensure that the cases reviewed are useful to the legal community in general.